Association of polymorphic gene variants of xenobiotic biotransformation enzymes with susceptibility to pulmonary tuberculosis - M. A. Alymenko; R. Sh. Valiev; A. V. Polonikov; T. N. Golubeva; A. P. Vasilevskaya; E. V. Miroshnik (Туберкулез и болезни лёгких)
The objective: to investigate the relationship of polymorphic variants of genes of xenobiotic biotransformation metabolism enzymes (NAT2 (590G>A (rs1799930)), CYP2E1 (9896C>G (rs2070676)), ABCB1 (3435T>C (rs1045642)), GSTM1 (E/D), GSTT1 (E/D) with the risk of pulmonary tuberculosis.Subjects and Methods. Within the framework of this study, a population sample of unrelated 1081 individuals of Slavic nationalities (mainly Russians) living in the territory of Kursk Oblast was used.Results. The del/del (D/D) GSTM1 genotype was associated with an increased risk of developing tuberculosis, while carrying the del/del (D/D) GSTT1 genotype was associated with a lower risk of developing the disease. Polymorphism 3435T>C ABCB1 (TC genotype) was associated with increased susceptibility to pulmonary tuberculosis in the codominization model, while TT+TC genotypes had the same association in the dominance model.